2019
DOI: 10.2478/saeb-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ Creativity Development within Innovative Processes of Enterprise

Abstract: Business practice requires creativity to be considered an important part of management because innovation is the result of it. The aim of the paper is to find out how is the creativity of employees supported in food enterprises in Slovakia. After evaluating the information obtained from structured interview and questionnaire based on the 5-degree Likert scale, there were used one way ANOVA Kruskal-Wallis test as well as Cronbach alpha and Spearman’s correlation tests. The survey also highlighted the significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Based on scientific publication of collective of authors Lušňáková et al (2019), food businesses in Slovakia show significant potential in the area of implementation of innovations and support of creativity of their employees. Even the research of authors Papula, Papulová (2013) in selected companies in Slovakia confirmed positive attitude of managers to support of creativity of employees as well as to understanding the significance of creativity, within its support at individual employees as well as at the development of competitive advantage and strategic direction of the whole company.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on scientific publication of collective of authors Lušňáková et al (2019), food businesses in Slovakia show significant potential in the area of implementation of innovations and support of creativity of their employees. Even the research of authors Papula, Papulová (2013) in selected companies in Slovakia confirmed positive attitude of managers to support of creativity of employees as well as to understanding the significance of creativity, within its support at individual employees as well as at the development of competitive advantage and strategic direction of the whole company.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring trends and the right preparation for these trends enable the company to obtain competitive advantage. Sustainability of the market position without innovations and creativity is not possible (Lušňáková, 2019). Even the employees of the selected companies appreciate support of their creativity from the management.…”
Section: Discussionmentioning
confidence: 99%